A review of oxytocin use for sows and gilts - S K Linneen; J M Benz; Joel M DeRouchey; Robert D Goodband; Michael D Tokach; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
Oxytocin is frequently used to decrease farrowing time and birth interval as an aid to prevent stillbirths, but recent research has shown that oxytocin use can increase the number of pigs stillborn when used too early in the birth process. The research indicated that the reason for increased stillbirths was an increased number of ruptured umbilical cords, leading to compromise of the pigs' oxygen supply during the birth process. Oxytocin usage should be limited to older-parity sows and the last half of the birth order.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Swine; Oxytocin; Stillbirth; Farrowing